Coronary Risk Factors and Collateral Circulation in Acute Myocardial Infarction - Sheila Sumargo; Julius B. Dewanto; Syarief Hidayat (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Coronary arterial stenosis, the major cause of acute myocardial infarction (AMI), induces shear stress to surrounding arteriolar endothelium. This stimulates changes in endothelial cells, smooth muscle cells and fibroblast to create collaterals that can provide alternative blood flow to the jeopardized myocardial area. However, coronary collateralization is various among AMI patients. The aim of this study was to analyze the correlation between coronary risk factors and collateral sirculation in AMI patients.Methods: A retrospective cross-sectional study was carried out to 148 medical records of hospitalized AMI patients in Dr. Hasan Sadikin General Hospital Bandung, Indonesia. All patients were assessed for coronary collateral circulation which were graded as good (Rentrop score 2–3) and poor (Rentrop score 0–1). Risk factors noted in this study were age group, sex, hypertension, diabetes mellitus and diagnosis (ST-segment Elevation Myocardial Infarction (STEMI) or Non STEMI (NSTEMI)) according to the medical record data. Results: Hypertension was found to be associated with the presence of good coronary collateral circulation (p=0.02, PR=1.410 [95% CI 1.030-1.930]). Sex, age group, diabetes mellitus and STEMI or NSTEMI diagnosis were not statistically significant.Conclusions: Hypertension was the only coronary risk factor associated to the presence of well-developed coronary collaterals. The increase of myocardial oxygen demand and flow of collateral feeding coronary artery in the setting of hypertension may contribute to the results. DOI: 10.15850/amj.v2n4.688